La obra literaria de Emilio Carrere (III): Emilio Carrere y sus poemarios Los ojos de los fantasmas, Nocturnos de otoño, La canción de las horas y El otoño dorado - Labrador Ben, Julia María; Sánchez Álvarez-insúa, ALBERTO (Dicenda. Estudios de lengua y literatura españolas, 2003)
This current essay continues the in-depth research of the literary works of the author Emilio Carrere Moreno (Madrid, 1881-1947). In this third study his poetic and literary biography is hereby completed, and his fifth, sixth, seventh and eighth Poem Collections are reviewed: The ghosts eyes (Los ojos de los fantasmas), Autumn nocturnes (Nocturnos de otoño), The hours song (La canción de las horas), and The golden autumn (El otoño dorado). Also discussed in this easy of his work, his literary criticism, and the structure and content of his poems. In addition, an index of first verses is also provided.